865. Methicillin-resistant Staphylococcus aureus (MRSA) prevalence among healthcare workers (HCW) in contact tracings in a Dutch teaching hospital, 2010-2018 - Weterings, veronica (Open Forum Infect Dis, 2020)
BACKGROUND: In The Netherlands, the national guidelines on MRSA prevention and control advocate screening of HCW after unprotected exposure to MRSA carriers. Although this strategy at large is successful, contact tracing of staff is a time consuming and costly component. We evaluated our contact tracing policy for HCW over the years 2010 – 2018. MRSA prevalence among samples in contact tracing [Image: see text] METHODS: A retrospective, observational study was performed in a Dutch teaching hospital. All HCW who had unprotected contact with an MRSA carrier were included in contact tracing. When there had been a long period of unprotected admission prior to an MRSA finding, or when the index case was a HCW, than the entire (nursing) team was tested. All samples of HCWs who were tested for MRSA carriage as part of contact tracing from 2010 until 2018 were included. A pooled nose, throat and perineum swab was collected using the eSwab medium (Copan) and inoculated on chromID MRSA agar plates (bioMérieux) after enrichment in a broth. RESULTS: In total, we included 8,849 samples (range: 677 – 1,448 samples per year) from a total of 287 contact tracings (range: 26 – 55 contact tracings per year). Thirty two HCWs were colonized with MRSA (0.36%; 95%CI 0.26 – 0.51). None of them developed a clinical infection. Eight HCWs (0.10%; 95%CI 0.05% – 0.19%) were colonized with the same MLVA type as the index case, and were detected in 6/287 contact tracings (2%). In 4/8 of these cases, a positive HCW was the index for undertaking contact tracing. In 3/8 cases it was clear that the HCW who was identified in the contact tracing was the source of the outbreak and was the cause of invasive MRSA infections in patients. Notably, a different MLVA type as the index case was found in 24 HCWs (0,27%; 95%CI 0,18 – 0,40) of which 7/24 HCW (29,2%) were intermittent carriers. CONCLUSION: This study revealed a sustained low MRSA prevalence among samples in contact tracing of healthcare workers, over nine years. Furthermore, it shows that when MRSA contact tracing is performed according to the national guideline only 1 out 1000 samples results in a secondary case. This is similar to the population carriage rate of MRSA in The Netherlands. More frequently, an unrelated strain is found. These findings raise question marks regarding the efficacy of the current strategy to perform contact tracing after unprotected exposure. DISCLOSURES: All Authors: No reported disclosures